TAX AVOIDANCE DIPENGARUHI PROFITABILITY, LEVERAGE, COMPANY SIZE, CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN SEKTOR ENERGY SUB SEKTOR COAL PRODUCTION YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2021 - Prayogi, Ilham; Rudianti, Walid; Ainiyah, Ghonimah Zumroatun; Yubiharto, Yubiharto (Medikonis, 2024)
ABSTRACK Tax evasion is an unauthorized attempt to reduce the tax burden by violating applicable laws. On the other hand, tax avoidance is a legitimate effort to reduce the tax burden by exploiting existing legal loopholes. Several factors can affect a company's tax obligations, including the level of Profitability, leverage, company size, and corporate social responsibility (CSR), as well as other factors. In this study, the authors chose companies in the energy sector, especially the coal production subsector, because companies in that sector are significant tax contributors in Indonesia. Therefore, the authors hypothesize that tax avoidance efforts will increase, which has implications for lower tax avoidance rates. The purpose of this study is to examine the effect of Profitability, leverage, company size, and corporate social responsibility (CSR) on tax avoidance. This research is a quantitative descriptive study that uses pre-existing data. The study population consisted of 40 companies. Sampling was carried out purposively, by selecting 24 companies as research samples. The analysis method used in this study is Multiple Linear Regression, and SPSS software is used as an auxiliary tool in conducting data analysis. The results showed a partial relationship that Profitability, company size, corporate social responsibility have a positive effect on tax avoidance, and leverage has a negative effect on tax avoidance. Based on the results of the study, it shows that the variables of Profitability, leverage, company size, and corporate social responsibility (CSR) affect tax avoidance with an R square percentage of 56.1%.